The Role of Muay Thai Training in Improving Physical Fitness and VO₂max in Sedentary Adults: A Narrative Review - Al Husni Hadi Pasca Putra; Julia Windi Gunadi; Yenni Limyati; Oeij Anindita Adhika (Jurnal Medika Malahayati, 2026)
Aging is a physiological process that results in a gradual decline in physical fitness. Sedentary lifestyles are spreading throughout the world due to a limited availability of spaces for physical activity, coupled with more sedentary lifestyles resulting from office-based jobs and the widespread use of televisions and video devices, which has led to an increase in inactivity and numerous harmful effects on health. Exercise with various modalities can maintain several components of physical fitness, thereby slowing or mitigating the negative effects of aging on physical fitness. Muay Thai is a famous martial arts sport from Thailand. A martial arts-based physical training program with "hard" movements can provide benefits in physical fitness components, such as cardiovascular fitness and muscle strength or endurance. The review aims to examine and synthesize current scientific evidence on how Muay Thai training influences maximal oxygen uptake (VO₂max) and various components of physical fitness in adults, with a particular focus on its potential role as an effective anti-aging intervention for individuals leading sedentary or secondary lifestyles. Literature search using Google Scholar, PubMed, Scopus with the keywords "(muay thai) AND (untrained OR cardiorespiratory OR sedentary). A total of 11 studies met the inclusion criteria, including randomized controlled trials and various intervention studies in adults. The findings indicate that Muay Thai training, particularly in previously untrained individuals, is associated with improvements in VO₂max and other physical fitness components, with increases of approximately 15–30% after 8–13 weeks. It is also linked to enhanced cardiovascular capacity, muscular strength and endurance, balance, coordination, and improvements in cardiometabolic risk factors such as blood pressure. However, most studies focus on trained athletes, highlighting the need for further research in non-athletic and older populations using more robust study designs.